The main characteristics and application of the shape memory alloys in orthodontics and endodontics - Jokanović Vukoman; Čolović Božana; Živković-Sandić Marija (Serbian Medical Society - Dental Section, Belgrade, 2019)
Main characteristics of shape memory alloys (SMA) based on equiatomic nickel-titanium (TiNi) composition and their application in endodontics were analyzed in this paper. Particularly, phase transition between cubic body centered austenite phase and orthorhombic or monoclinic martensite phase was studied. Besides, main drawbacks of the conventional technology of SMA production were given, as well as a new technology approaches in enhancement of SMA properties, without changes of their super-elasticity.